2018
DOI: 10.1001/amajethics.2018.812
|View full text |Cite
|
Sign up to set email alerts
|

How Should Primary Care Physicians Respond to Direct-to-Consumer Genetic Test Results?

Abstract: In this case, a primary care physician is presented with direct-toconsumer genetic test results and asked to provide counseling and order follow-up diagnostics. In order to deal effectively with this situation, we suggest physicians need look no further than the practice principles that guide more routine clinical encounters. We examine the rationale behind 2 major clinical ethical considerations: (1) physicians have obligations to help their patients achieve reasonable health goals but are not obligated to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…These findings can be expected as our study was performed in an area where consumer-initiated genetic testing had just become reported by studies that surveyed practicing physicians (Bernhardt et al, 2012;Powell et al, 2012). These findings were consistent with et al, 2018), and when to refer patients to clinical geneticists (Artin et al, 2019;Brothers & Knapp, 2018). Also, physicians should be informed that they should respond to patients respectfully and not ignore their use of consumer-initiated genetic tests, as this could jeopardize the provider-patient relationship (Artin et al, 2019) et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…These findings can be expected as our study was performed in an area where consumer-initiated genetic testing had just become reported by studies that surveyed practicing physicians (Bernhardt et al, 2012;Powell et al, 2012). These findings were consistent with et al, 2018), and when to refer patients to clinical geneticists (Artin et al, 2019;Brothers & Knapp, 2018). Also, physicians should be informed that they should respond to patients respectfully and not ignore their use of consumer-initiated genetic tests, as this could jeopardize the provider-patient relationship (Artin et al, 2019) et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Yet the availability of DTC health-related products has generated significant concerns by professionals. While some commentators and clinicians reportedly feel comfortable assisting their patients to interpret these results [ 14 , 15 ], others worry that healthcare providers are ill-prepared or unwilling to assist test recipients who seek advice and medical interventions [ 16 20 ] and that these results could increase health care utilization and divert resources from more pressing issues [ 21 23 ]. Indeed, several studies indicate that some consumers do seek medical advice but they are not always satisfied [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study has found that the use of DTC testing lack standardised laboratory practices and is prone to misclassification in risk assessment and should be used with caution for clinical care decisions. 91 This may pose as a risk for GPs who could be less attuned to the heightened levels of scrutiny towards DTC testing and accept genetic test results at face value. 90 Yet, GPs remained well positioned to assist their patients in informing their family members about genetic testing options in view of their long-standing relationship.…”
Section: Discussionmentioning
confidence: 99%